The Effect of Training, Discipline, and Commitment on the Performance of the Great Surabaya Cadres (KSH) in Medokan Ayu Sub-District, Surabaya - Trianti; Rifki Suwaji (MUTIARA: Jurnal Ilmiah Multidisiplin Indonesia, 2026)
The performance of Kader Surabaya Hebat (KSH) plays a crucial role in supporting the success of community service programs implemented by the Surabaya City Government. Variations in the levels of training, work discipline, and organizational commitment are presumed to influence the quality of cadre performance and therefore require empirical investigation. This study aims to analyze the effects of training, work discipline, and organizational commitment on the performance of KSH in Medokan Ayu Sub-district, Surabaya. The research employed a quantitative approach with an associative research design involving 30 cadres selected through purposive sampling. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS 4 software. The findings reveal that training has a positive and significant effect on performance (β = 0.312; p = 0.008), work discipline has a positive and significant effect on performance (β = 0.354; p = 0.004), and organizational commitment exerts the strongest positive and significant effect on performance (β = 0.421; p = 0.001). These results indicate that improving cadre performance requires the integrated enhancement of competencies, work discipline, and organizational commitment. The novelty of this study lies in its empirical evidence demonstrating that organizational commitment is the most dominant factor in improving cadre performance within community-based public service organizations, thereby extending the human resource management literature in the context of grassroots public service delivery.